The Global Landscape of Occupational Exposure Limits-Implementation of Harmonization Principles to Guide Limit Selection - Deveau, M.; Chen, C-P; Johanson, G.; Krewski, D.; Maier, A.; Niven, K. J.; Ripple, S.; Schulte, P. A.; Silk, J.; Urbanus, J. H.; Zalk, D. M.; Niemeier, R. W. (Journal of occupational and environmental hygiene, 2015)
Occupational exposure limits (OELs) serve as health-based benchmarks against which measured or estimated workplace exposures can be compared. In the years since the introduction of OELs to public health practice, both developed and developing countries have established processes for deriving, setting, and using OELs to protect workers exposed to hazardous chemicals. These processes vary widely, however, and have thus resulted in a confusing international landscape for identifying and applying such limits in workplaces. The occupational hygienist will encounter significant overlap in coverage among organizations for many chemicals, while other important chemicals have OELs developed by few, if any, organizations. Where multiple organizations have published an OEL, the derived value often varies considerably-reflecting differences in both risk policy and risk assessment methodology as well as access to available pertinent data. This article explores the underlying reasons for variability in OELs, and recommends the harmonization of risk-based methods used by OEL-deriving organizations. A framework is also proposed for the identification and systematic evaluation of OEL resources, which occupational hygienists can use to support risk characterization and risk management decisions in situations where multiple potentially relevant OELs exist.